Content Analysis of Indonesian Cultural on EFL Textbook Published by Indonesian Ministry of Education and Culture - Normalela Normalela; Absharini kardena (Universitas Pahlawan Tuanku Tambusai, 2022)
As an unquestionably helpful instrument, textbooks should fulfill the criteria of effective textbook such as cultural value that reflects the nation’s values and ideas. This research analyzed an English textbook of grade nine Junior High School used in Indonesia based on cultural perspective. It occurs since Indonesian students should focus more on their culture rather than target language culture as a demand of Indonesian national education system. In order to analyse the book systematically and comprehensively, this research used Byram’s cultural content theory. Byram’s theory is considered comprehensive and sufficient that consist of nine criterion. The result showed that the textbook being analysed covered seven from nine criterion based on Byram’s theory. This finding indicated that there is a demand to revise English textbook of nine grade on Junior High School in order to improve the contribution of textbook towards Indonesian education itself.As an unquestionably helpful instrument, textbooks should fulfill the criteria of effective textbook such as cultural value that reflects the nation’s values and ideas. This research analyzed an English textbook of grade nine Junior High School used in Indonesia based on cultural perspective. It occurs since Indonesian students should focus more on their culture rather than target language culture as a demand of Indonesian national education system. In order to analyse the book systematically and comprehensively, this research used Byram’s cultural content theory. Byram’s theory is considered comprehensive and sufficient that consist of nine criterion. The result showed that the textbook being analysed covered seven from nine criterion based on Byram’s theory. This finding indicated that there is a demand to revise English textbook of nine grade on Junior High School in order to improve the contribution of textbook towards Indonesian education itself.Keywords:English textbook, Indonesian culture, analysis.